Cognitive behavioral therapy in practice: therapist perceptions of techniques, outcome measures, practitioner qualifications, and relation to research. Issue 5 (3rd September 2017) - Bohman, Benjamin; Santi, Alberto; Andersson, Gerhard
Abstract: Cognitive behavioral therapy (CBT) has a strong evidence base for several psychiatric disorders, however, it may be argued that currently there is no overall agreement on what counts as 'CBT'. One reason is that CBT is commonly perceived as encompassing a broad range of treatments, from purely cognitive to purely behavioral, making it difficult to arrive at a clear definition. The purpose of the present study was to explore practicing therapists' perceptions of CBT. Three hundred fifty members of two multi-disciplinary interest groups for CBT in Sweden participated. Mean age was 46 years, 68% were females, 63% psychologists and mean number of years of professional experience was 12 years. Participants completed a web-based survey including items covering various aspects of CBT practice. Overall, therapist perceptions of the extent to which different treatment techniques and procedures were consistent with CBT were in line with current evidence-based CBT protocols and practice guidelines, as were therapists' application of the techniques and procedures in their own practice. A majority of participants (78%) agreed that quality of life or level of functioning were the most important outcome measures for evaluating treatment success. Eighty percent of therapists believed that training in CBT at a basic level was a requirement for practicing CBT. There was a medium size Spearman correlation of r s= .46 between the perceived importance of research to practice and the extent to which participants kept themselves updated on research. Implications for training, quality assurance, and the effectiveness of CBT in clinical practice are discussed.